The Historical Evolution of the Social Cognitive Construction of Disability - Jingran ZHANG (Yixue yu zhexue)
The construction of disability cognition has gone through four stages. In early societies, disability was typically interpreted through a moral perspective. With the enlightenment and advancements in science, medicine gradually became the dominant explanatory framework, driving the formation of rehabilitation treatment cognition as well as innovations in related social systems and technologies. Since the 1960s, the social recognition emphasizing that the "disability status" is the result of the interaction between individuals and their social environment has gradually become mainstream. Disability cognition has been influenced by multiple factors, including economic progress, medical breakthroughs, social attitude shifts, and cultural changes. Based on the social construction theory, this paper aims to explain how sociocultural changes shape and influence disability cognition, providing a solid theoretical foundation and profound historical insights for understanding and supporting the disability community.